Evaluation of the implementation of the School Feeding Program in Cali. The PAE at the blackboard - Zapata, Christian (Cuadernos de Administración, 2024)
The aim of this article is to assess the execution of the School Feeding Program (Programa de Alimentación Escolar) [PAE] in Cali between 2016 and 2019, focusing on its role in promoting healthy eating habits. Clear, concise language and technical terms have been employed, with an objective and balanced approach throughout. The study used documentary analysis to explore the program’s development at both national and local levels, as well as the impact of new public management strategies since its establishment in 1936. In addition, stakeholder interviews were conducted and analyzed alongside program documents using the thematic networks methodology to characterize the program based on its theory. The primary findings suggest that while the program is effective, there are implementation flaws. As a result, adjustments in the design of the school feeding program are essential to gradually attain effect indicators. The results constribute to the construction of evaluative knowledge on new public management processes, in particular, in relation to effectiveness.